FEATURES OF ANXIETY MANIFESTATION IN PRESCHOOL CHILDREN DURING THE ADAPTATION PROCESS TO PRESCHOOL EDUCATION INSTITUTIONS (Psychology Travelogs, 2024)
The article is devoted to a rather topical topic today, namely, increased anxiety in preschool children. This problem is actively studied by Ukrainian and foreign scientists, who investigate the causes and factors that contribute to the development of anxiety disorders in children. The paper highlights the experience of researching the problem of high anxiety of some foreign and domestic scientists in relation to the concepts of «anxiety», «anxiousness», «preschool age», «adaptation», «maladjustment».The article describes the main types of anxiety (situational, which is caused by a certain situation that actually causes a state of anxiety and personal, which is a peculiar property of the personality), the destructive effect on the child's psyche and the impact of increased anxiety on the child's adaptation to preschool education. Most often, the causes of its occurrence in childhood can be the peculiarity of the nervous system, past illnesses, family relationships, methods of education, and the environment in which the child is. It is argued that high anxiety negatively affects not only the degree of adaptation to new conditions but also the formation of a preschooler as a person in society. The author analyzes in detail the conditions of maladjustment, the problems when children, for various reasons, cannot adapt to the conditions of the environment on an equal footing with their peers, and highlights the main consequences of this process. The authors offer recommendations to educators and parents on how to reduce and prevent maladjustment in preschool education.The article reveals the theoretical and practical aspects of anxiety, its relevance and impact on child development and mental health in general. Therefore, its detection at early stages is of great importance and research should focus on developing methods to reduce anxiety among preschool children.
Keywords: preschool age; anxiety; manifestations of anxiety; adaptation; maladjustment